Study of Polyphenol Content and Antioxidant Properties of Various Mix of Chocolate Milk Masses with Different Protein Content - Bogumiła Urbańska; Tomasz Szafrański; Hanna Kowalska; Jolanta Kowalska (MDPI AG, 2020)
The aim of the study was to analyze the antioxidant character of conched chocolate milk masses, taking into account different protein content in milk. For the study, cocoa liquor obtained from roasted and unroasted cocoa beans from different regions, as well as milk powder obtained by spray and cylindrical drying were used. The analysis that was carried out showed that the protein content of powdered milk products ranged from about 11.6% (w/w) to over 31% (w/w). Lower content of polyphenols and lower antioxidant activity were shown in the masses to which the addition of milk with higher protein content was applied. The analysis of antioxidant character of chocolate milk masses showed higher total polyphenols content in masses prepared from unroasted cocoa beans liquor.